The mediating role of psychological resilience in the effect of strength of religious faith on coping with stress in people with type 2 diabetes: A SEM analysis - Ozturk, Zeynep; Turan, Gulcan Bahcecioglu; Donmez, Orhun (Wiley, 2024)
Aim: This study was conducted to examine the mediating role of psychological resilience in the effect of strength of religious faith on coping with stress in people with type 2 diabetes. Design: This study has a cross-sectional descriptive-analytical study. Methods: It was conducted with 184 people with type 2 diabetes who were admitted to a family health centre in Erzurum, the east of Turkey. The data were collected by using the 'Santa Clara Strength of Religious Faith Questionnaire', 'Brief Resilience Scale (BRS)' and 'Scale of Ways of Coping With Stress (SWCS)'. The study was reported by following the STROBE recommendations. Structural equation modelling and bootstrapping method were used to analyse the data. This study was reported following the STROBE recommendations. Results: In the study, according to the model, the direct effect of strength of religious faith on SWCS (beta = 0.564; p < 0.01) and BRS (beta = 0.545; p < 0.01) was moderate, positive and significant. In addition, the effect of resilience on coping with stress (beta = 0.320; p < 0.01) was also found to be moderate, positive and significant. The total effect of strength of religious faith on coping with stress mediated by resilience (beta = 0.738; p < 0.01) was found to be highly positive and significant. The model explains 61.7% of the variance in coping with stress. Fit index values according to the model were found as chi(2) = 2368.02, df: 980, chi(2)/df 2.368, RMSEA 0.088, CFI 0.773, TLI 0.760 and SRMR 0.083. It was found that strength of religious faith had a positive effect on coping with stress in people with type-2 diabetes, and this effect was strengthened by the mediating role of psychological resilience. Patient or Public Contribution: This study shows the effect of religious belief and psychological resilience in increasing the coping skills of people with type-2 diabetes. Therefore, taking religious beliefs and spirituality into consideration in nursing care may increase patients' coping skills.
Keywords: nurse; patient; psychological; religious; resilience; stress; type 2 diabetes